Using information/inspiration as a sustainable design tool - Tracy Bhamra; Vicky Lofthouse (2003)
This paper presents the results of research ongoing to establish useful tools for designers to aid them in the process of sustainable design. The research has developed a greater understanding of the type of criteria required of a sustainable design tool in order to make it more appropriate and useful to designers. One of the deliverables of this project has been a web based sustainable design tool that combines sustainable design information with a selection of inspirational concepts. The research is hoping to educate designers to ensure that environmental problems are addressed at the early stages of product development, resulting in more innovative solutions. In addition the research is providing many examples of projects where sustainable design has been beneficial to companies, and led to improved products. This paper will present the results to date of the research, the current tool and results of its use.